PENGARUH PEMBELAJARAN BERBASIS PROYEK (PJBL) BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA SEKOLAH DASAR PATUK II GUNUNGKIDUL, YOGYAKARTA - Bara Saputro, Hengkang; Oktavia, Lusi (Jurnal Dikdas Bantara, 2025)
This study aims to determine the effect of the ethnomathematics-based PJBL learning model on improving students' numeracy literacy skills in reading and writing numbers at Patuk II Public Elementary School, Gunungkidul. This research was motivated by students' low numeracy literacy skills, characterized by difficulty understanding basic mathematical concepts and low interest in learning. The research method used was quantitative with a one- group pretest-posttest design. The study sample involved 18 fourth-grade students at Patuk II Public Elementary School, Gunungkidul. Data were collected through observation, testing, and documentation. The research instrument consisted of essay questions designed to measure students' numeracy literacy, specifically on the topic of plane figures related to the local cultural context. The results showed that the implementation of ethnomathematics- based PJBL significantly improved students' numeracy literacy skills. The average pretest score of 46.39 increased to 84.33 in the posttest. Hypothesis testing using a paired sample t-test yielded a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest results. Thus, it can be concluded that the ethnomathematics-based PJBL model is effective in improving elementary school students' numeracy literacy skills.